Serum Calcium Levels and Parkinson’s Disease: A Mendelian Randomization Study - Wang, Yanchao; Gao, Luyan; Lang, Wenjing; Li, He; Cui, Pan; Zhang, Nan; Jiang, Wei (Frontiers in Genetics, 2020)
Background Though increasing epidemiological studies have evaluated the correlation between serum calcium contents and Parkinson’s disease (PD), the results are inconsistent. At present, whether there is a causal association between serum calcium content and PD remains undetermined. Objective and Methods This study was designed to explore the relationship between increased serum calcium contents and PD risk. In this present study, a Mendelian randomization trial was carried out using a large-scale serum calcium genome-wide association study (GWAS) dataset (N = 61,079, Europeans) and a large-scale PD GWAS dataset (N = 8,477, Europeans including 4,238 PD patients and 4,239 controls). Here, a total of four Mendelian randomization methods comprising weighted median, inverse-variance weighted meta-analysis (IVW), MR-Egger, and MR-PRESSO were used. Results Our data concluded that genetically higher serum calcium contents were not significantly related to PD. Conclusion In conclusion, we provided genetic evidence that there was no direct causal relationship between serum calcium contents and PD. Hence, calcium supplementation may not result in reduced PD risk.